2020
DOI: 10.1111/mmi.14479
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the main glutamine and glutamate transporters in Staphylococcus aureus and their impact on c‐di‐AMP production

Abstract: A Staphylococcus aureus strain deleted for the c‐di‐AMP cyclase gene dacA is unable to survive in rich medium unless it acquires compensatory mutations. Previously identified mutations were in opuD, encoding the main glycine‐betaine transporter, and alsT, encoding a predicted amino acid transporter. Here, we show that inactivation of OpuD restores the cell size of a dacA mutant to near wild‐type (WT) size, while inactivation of AlsT does not. AlsT was identified as an efficient glutamine transporter, indicatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Recent work in S. aureus and B. subtilis identified suppressor mutations in Gln and Glu transporters, respectively, which rescued the growth of mutants devoid of c-di-AMP (9,38). These results align well with those found in L. lactis and suggest that cells defective in c-di-AMP production are unable to regulate intracellular levels of major osmolyte amino acids.…”
supporting
confidence: 76%
“…Recent work in S. aureus and B. subtilis identified suppressor mutations in Gln and Glu transporters, respectively, which rescued the growth of mutants devoid of c-di-AMP (9,38). These results align well with those found in L. lactis and suggest that cells defective in c-di-AMP production are unable to regulate intracellular levels of major osmolyte amino acids.…”
supporting
confidence: 76%
“…aureus suppressor mutants resulted in the identification of the AlsT glutamine transporter, thus indicating that glutamine rather than glutamate is toxic for the S . aureus Δ dac mutant [ 39 , 42 ]. Again, these differences between the related organisms support the idea that c-di-AMP has global overarching functions in the different bacteria, but these can be put into practice differently.…”
Section: Discussionmentioning
confidence: 99%
“…In S . aureus , c-di-AMP is dispensable for growth on complex medium under anaerobic conditions or when the bacteria acquire suppressor mutations that affect osmolyte or glutamine uptake [ 40 , 42 ]. Both types of studies support the idea that the control of potassium and osmolyte homeostasis is the central essential function of c-di-AMP in many bacteria that produce it [ 43 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of the predicted glutamine transporter GlnPQ increased TCA cycle activity, decreased polysaccharide intercellular adhesin biosynthesis, and significantly reduced virulence in a rabbit endocarditis model [ 12 ]. Recently it was demonstrated that GlnPQ does not transport glutamine and that AlsT is instead the main glutamine transporter [ 9 ]. Moreover, AlsT-mediated glutamine uptake decreased c-di-AMP levels, which is known to effect cell envelope homeostasis, virulence and β-lactam resistance [ 9 , 25 ].…”
Section: Why Investigate Amino Acid and Peptide Transporters As Potenmentioning
confidence: 99%
“…Recently it was demonstrated that GlnPQ does not transport glutamine and that AlsT is instead the main glutamine transporter [ 9 ]. Moreover, AlsT-mediated glutamine uptake decreased c-di-AMP levels, which is known to effect cell envelope homeostasis, virulence and β-lactam resistance [ 9 , 25 ].…”
Section: Why Investigate Amino Acid and Peptide Transporters As Potenmentioning
confidence: 99%